2022
DOI: 10.1007/s40750-022-00208-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Pathogen Disgust Increased on Days of the Menstrual Cycle when Progesterone is High? Evidence from a Between-Subjects Study Using Estimated Progesterone Levels

Abstract: Objective The Compensatory Prophylaxis Hypothesis proposes that women will show increased pathogen disgust at points in the menstrual cycle when progesterone is high, compensating for the immunosuppressive effects of progesterone. However, evidence for the Compensatory Prophylaxis Hypothesis from studies that used longitudinal designs to investigate whether pathogen disgust tracks changes in progesterone is mixed. It was recently proposed that longitudinal designs may be poorly suited to testing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Curtis et al ( 2004 ) showed that disgust sensitivity declines with age, therefore, it is important to attempt to replicate these findings with older adults and with participants from different cultures. However, Raifee et al ( 2022 ) did not find any evidence for age-related declines in pathogen disgust. Third, in this study we only tested the role of short-term mating and its association with viewing pathogen cues.…”
Section: Discussionmentioning
confidence: 93%
“…Curtis et al ( 2004 ) showed that disgust sensitivity declines with age, therefore, it is important to attempt to replicate these findings with older adults and with participants from different cultures. However, Raifee et al ( 2022 ) did not find any evidence for age-related declines in pathogen disgust. Third, in this study we only tested the role of short-term mating and its association with viewing pathogen cues.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, two longitudinal studies, one of which again used video stimuli [17] and the other used a text-based questionnaire [18], also failed to find evidence supporting this hypothesis. The results of a cross-sectional study conducted by Rafiee et al [19], which observed the relationship between estimated levels of progesterone and estradiol and pathogen-related disgust, also found no supporting evidence. On the other hand, the results of two different longitudinal studies do support the compensatory prophylaxis hypothesis: they found that women had higher disgust sensitivity during the luteal phase than during menstruation [20] or the follicular phase [21].…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, later cross-sectional studies -one that used video stimuli to elicit disgust [15], another that applied two different disgust scales [16], and two longitudinal studies, one of which again used video stimuli [17] and the other used the Three Domains of Disgust Scale [18] -found no evidence in support of the compensatory prophylaxis hypothesis. The results of a cross-sectional study by Rafiee et al [19], which observed the relationship between estimated (based on the calculated day of the cycle) levels of progesterone and estradiol, and scores on the Pathogen domain of the Three Domains of Disgust Scale, also found no supporting evidence. On the other hand, the results of two other longitudinal studies do support the compensatory prophylaxis hypothesis: they found that women had higher disgust sensitivity during the luteal phase than during menstruation [20]or during the follicular phase [21].…”
Section: Introductionmentioning
confidence: 92%